Exercise-to-rest ratios in repeated sprint ability training in women`s soccer - Ruscello, B.; Esposito, M.; Partipilo, F.; Di Cicco, D.; Filetti, C.; Pantanella, L.; D'Ottavio, S. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The aim of this study was to investigate the applicability of three different exercise-to-rest ratios in repeated sprint ability (RSA) training in women`s soccer players, applying those which are usually adopted in male adult and young players, when performing three different sprinting modes (straight, shuttle, and sprinting with changing of direction). METHODS: Fifteen trained female soccer players (height: 1.65±0.06 m; weight: 59.3±9.0 kg; BMI 21.6±2.7 kg/m2; age: 23.3±5.9 years) participated to the study. In order to compare the different values of the time recorded, an index of fatigue (IF%) was used. Recovery times among trials in the sets were administered according to the 1:5, 1:3, 1:2 exercise-to-rest ratio, respectively. Blood lactate concentrations at the end of each set were analyzed. RESULTS: Significant differences among trials within each set (repeated measures ANOVA; P<0.05) were found, as evidence of fatigue over time, with an average decay of performance of about 5% but no significant differences were found in IF%, among the three different sprinting modalities when applying the investigated exercise-to-rest ratios (factorial ANOVA; P>0.05). Significant differences were found in blood lactate concentrations (P<0.05). CONCLUSIONS: The results of this study confirm that the exercise-to-rest ratios considered in this study might be suitable to design effective testing protocols and training sessions aimed at the development of the RSA in women`s soccer players, keeping the performances in the speed domain (IF% <7-8%) but inducing the fatigue processes sought with this kind of training method.